Um preso por vaga: estratégias políticas e judiciais de contenção da superlotação carcerária - Coelho, Priscila (2020)
This research aims to present the main arguments, mobilizations and interactions observed between actors in the criminal justice system, within the context of using two different strategies to limit prison overcrowding. The empirical corpus of the work include the experience of interdiction of overcrowded prison units located in the city of Aparecida de Goiânia, Goiás. The second strategy that composes the research refers to the implementation of the project called “Taxative Prison Occupation”, in the State of Paraná, whose objective was to limit the use of prison by managing the system's vacancies. The empirical material consists of documentary analysis, direct observation and interviews with the actors involved in the strategies addressed. In order to analyze the results, was used grounded theorizing (TFD) to categorize and organize the information obtained in the field, and systems theory to observe the distinctions that underlie the main arguments presented by the professionals involved with the actions. Based on the identification of these arguments, the research points to the existence of a conflict between the Executive and the Judiciary over the attribution on the problem of prison overcrowding. In addition, it demonstrates how the use of certain argumentative categories reflects the way in which prison is thought and used, even in a context of preventive imprisonment.